EMOTIONAL ROLE ADJUSTMENT AND MARITAL SATISFACTION OF MARRIED WORKING COUPLES IN IMO STATE, NIGERIA - Melvina Amalu; Nneka Sophie Amalu (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The purpose of the study was to examine the relationship between emotional role adjustment and marital satisfaction of married working couples in Mbaitoli local Government area of Imo State. One hypothesis was formulated to guide the study. The research design adopted was the Correlation research design. Sample of 170 married couples selected from a population of 1700 couples was used for the study. Marital Role Expectation Inventory (MREI) was employed for data collection.  The instrument has a reliability coefficient of .84 with split-half method. Pearson Product Moment Correlation (PPMC) was employed to analyze the data generated. Based on the finding, it was recommended among others that for the spouses to enjoy satisfaction in their relationship, there should be appreciation and positive feedback between them